Photocatalytic Intramolecular Allyl Migration of Silyl Enol Ethers - Xiang, Huimei; Liu, Haitang; Fu, Shaomin; Liu, Bo (Synlett, 2025)
A photocatalytic platform for allylic α-alkylation of carbonyl compounds through intramolecular oxidative allyl migration is developed. This metal-free protocol enables precise allyl assembly under mild conditions with high efficiency and broad substrate scope, encompassing the tolerance of the challenging quaternary carbon center and internal olefin derivatives. Mechanistic investigations reveal a radical-mediated cyclization pathway.
Keywords: Photo-induced electron transfer; Organic photocatalyst; Enol silyl ether; α-alkylation; 7-Endo-trig cyclization